2021
DOI: 10.3390/ma14143807
|View full text |Cite
|
Sign up to set email alerts
|

Ground Tire Rubber Filled Flexible Polyurethane Foam—Effect of Waste Rubber Treatment on Composite Performance

Abstract: The application range of flexible polyurethane (PU) foams is comprehensive because of their versatility and flexibility in adjusting structure and performance. In addition to the investigations associated with further broadening of their potential properties, researchers are looking for new raw materials, beneficially originated from renewable resources or recycling. A great example of such a material is ground tire rubber (GTR)—the product of the material recycling of post-consumer car tires. To fully exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…The improvement suggests a sufficient strength of the interfacial interactions between the SFP, LG-SFP, and PUR matrix. It was particularly pronounced when SFP was used because of the shape and oil fraction on the surface of the particles, which, together with the reduced average cell size, promotes the tensile strength by the facilitated stress distribution [ 44 ]. Even though the tensile strength of LG-SFP particles modified PUR foams increases, the rise is lower compared to SFP particles modified PUR foams.…”
Section: Resultsmentioning
confidence: 99%
“…The improvement suggests a sufficient strength of the interfacial interactions between the SFP, LG-SFP, and PUR matrix. It was particularly pronounced when SFP was used because of the shape and oil fraction on the surface of the particles, which, together with the reduced average cell size, promotes the tensile strength by the facilitated stress distribution [ 44 ]. Even though the tensile strength of LG-SFP particles modified PUR foams increases, the rise is lower compared to SFP particles modified PUR foams.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the cross-linked structure and elasticity of car tires, the process of grinding them consumes a lot of energy. The obtained recyclate can be used as a filler in cross-linked polymeric matrices [ 13 , 14 , 15 , 16 ]. The application of rubberized asphalt to construct pavements or the use of GTR as a modifier to the concrete are additional methods of recycled tire use [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hejna et al [168,169] studied the effect of treated ground tire rubber (GTR) (treatment by various natural oils, KMnO 4 , or H 2 O 2 ) on polyurethane/GTR composite foams. Presented results showed that suitable modification of ground tire rubber is a promising approach for tailoring the structure and performance of polyurethane composite foams.…”
Section: Polyurethane Composite Foamsmentioning
confidence: 99%